Multiple Non-Species-Specific Pathogens Possibly Triggered the Mass Mortality in Pinna nobilis - Fabio Scarpa; Daria Sanna; Ilenia Azzena; Davide Mugetti; Francesco Cerruti; Sepideh Hosseini; Piero Cossu; Stefania Pinna; Daniele Grech; David Cabana; Viviana Pasquini; Giuseppe Esposito; et al. (Life, 2020)
The fan mussel, Pinna nobilis, represents the largest bivalve endemic to the Mediterranean Sea. Since 2016, dramatic mass mortality of this species has been observed in several areas. The first surveys suggested that Haplosporidium pinnae (currently considered species-specific) was the main etiological agent, but recent studies have indicated that a multifactorial disease may be responsible for this phenomenon. In this study, we performed molecular diagnostic analyses on P. nobilis, P. rudis, and bivalve heterologous host species from the island of Sardinia to shed further light on the pathogens involved in the mass mortality. The results support the occurrence of a multifactorial disease and that Mycobacterium spp. and H. pinnae are not necessarily associated with the illness. Indeed, our analyses revealed that H. pinnae is not species-specific for P. nobilis, as it was present in other bivalves at least three years before the mass mortality began, and species of Mycobacterium were also found in healthy individuals of P. nobilis and P. rudis. We also detected the species Rhodococcus erythropolis, representing the first report in fan mussels of a bacterium other than Mycobacterium spp. and Vibrio spp. These results depict a complicated scenario, further demonstrating how the P. nobilis mass mortality event is far from being fully understood.